Grey Wolf Optimizer Based Battery Energy Storage System Sizing for Economic Operation of Microgrid - Sukumar S.; Marsadek M.; Ramasamy A.; Mokhlis H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric batteries; Energy management; Energy management systems; Genetic algorithms; Integer programming; Operating costs; Particle swarm optimization (PSO); Artificial bee colonies (ABC); Battery energy storage systems; battery sizing; Gravitational search algorithm (GSA); Grey Wolf Optimizer; Meta-heuristic optimization techniques; Micro grid; Mixed integer linear programming (MILP); Battery storage